Ablation of lipocalin-2 reduces neuroinflammation in a mouse model of Krabbe disease - Jacob Favret; Malabika Maulik; Rayan Masoom; Meghana Kushwaha; Devin Thompson; Richard Browne; Daesung Shin (Scientific Reports)
Abstract Lipocalin-2 (LCN2) is an acute-phase secretory molecule significantly upregulated in various neuroinflammatory and demyelinating conditions. Krabbe disease (KD) is a neurodegenerative lysosomal disorder caused by a galactosylceramidase (GALC) deficiency, accumulating cytotoxic psychosine in nervous systems, and subsequent neuroinflammation. Here, we show that LCN2 is highly overexpressed in GALC-deficient astrocytes. To further understand if the elevated LCN2 is critical for KD progression, we globally deleted Lcn2 in the Galc-knockout (KO) mouse model. Interestingly, the Galc and Lcn2 double KO mice showed dramatically reduced neuroinflammation including gliosis. Pro-inflammatory cytokines such as TNF-α, MMP3, and MCP-1 were significantly downregulated in the brain of the double KO mice compared to Galc-KO. In addition, the ablation of Lcn2 marginally increased the survival and attenuated disease progression in Galc-KO mice. However, the accumulation of psychosine was not altered in the brain by LCN2 deficiency. Our findings suggest that the upregulation of LCN2 is crucial for the aggravation of neuroinflammation in a mouse model of Krabbe disease.